2001
DOI: 10.1007/bf03343887
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral testicular adrenal rest tissue in congenital adrenal hyperplasia: US and MR features

Abstract: We describe magnetic resonance (MR) and ultrasonography (US) features of bilateral testicular adrenal rest tissue in a 20-yr-old man with congenital adrenal hyperplasia (CAH). Scrotal ultrasonology detected bilateral homogeneous hypoechoic lesions with well-defined margins and without evidence of sound attenuation. MR is useful in defining the size of lesions, because the contrast resolution is better than with sonography and allows an accurate definition of the extent of disease. This case suggests that US ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 9 publications
5
23
0
3
Order By: Relevance
“…Also, the lesions were isointense to muscle on T1-and T2-weighted images, features resembling normal adrenal glands. In previous reports of MR studies, similar features have been described, but Avila et al [8] also found 4 of 14 lesions that were hyperintense on T1, compared with normal testicular tissue [16,17]. Intravenous gadolinium resulted in enhancement of the lesions in 13 of 15 patients.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Also, the lesions were isointense to muscle on T1-and T2-weighted images, features resembling normal adrenal glands. In previous reports of MR studies, similar features have been described, but Avila et al [8] also found 4 of 14 lesions that were hyperintense on T1, compared with normal testicular tissue [16,17]. Intravenous gadolinium resulted in enhancement of the lesions in 13 of 15 patients.…”
Section: Discussionsupporting
confidence: 57%
“…The testicular masses in CAH show altered echogenicity compared with normal testicular tissue: in most studies hypoechogenicity of the lesions is reported [5,6,8,9,12,13,14,15,16]. We found that echogenicity was related to lesion size: 17 of the 20 lesions <2 cm where hypoechoic, whereas all lesions >2 cm were hypoechoic with hyperechoic reflections.…”
Section: Discussionmentioning
confidence: 57%
“…Most of these lesions are located inside of or close to the testicular hilus (86%), and they are usually bilateral (83%-100%). 2 Magnetic resonance imaging (MRI) can be used as a problem-solving modality in difficult cases. On MRI, these testicular adrenal rests are isointense on longitudinal relaxation time-weighted images and hypointense on transverse relaxation time-weighted images and are diffusely enhanced on post-gadolinium-enhanced images.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital testicular adrenal rests are seen in about 29% of patients with congenital adrenal hyperplasia (CAH) (54,55). CAH is an autosomal recessive disease characterized by a deficiency of adrenocortical enzymes, particularly 21-hydroxylase.…”
Section: Congenital Testicular Adrenal Restsmentioning
confidence: 99%
“…15) (54). Intratesticular masses are typically located in the region of the mediastinum testis (in 86%) (55). Ultrasound is the modality of choice for their diagnosis; however, MRI can also assist as a problem-solving modality in some cases.…”
Section: Congenital Testicular Adrenal Restsmentioning
confidence: 99%